KONSTRUK MODEL KEPUASAN KERJA DAN BEBAN KERJA KARYAWAN TERHADAP KINERJA KARYAWAN BERBASISKAN CORE VALUE KEUNGGULAN BERSAING BERKELANJUTAN PERUSAHAAN DI PT XYZ - Silvia Gracelia, (2022)
PT XYZ is a trading company, which helps producers of cosmetic, food, pharmaceutical and health raw materials with the resulting products in the form of plant extraction (from roots, stems, leaves, flowers to fruit). Based on the results of distributing pre-survey questionnaires, interviews and field observations, problems were encountered regarding job satisfaction, workload, and employee performance. This study aims to construct a model of job satisfaction, employee workload on employee performance based on the core value of the company's sustainable competitive advantage. Questionnaires were distributed to PT XYZ factory employees as many as 104 respondents. This study used the Structural Equation Modeling (SEM) method which was then processed using AMOS software. The research shows that the variables of customer satisfaction and workload have a significant effect on employee performance and employee performance have a significant effect on sustainable competitive advantage.